2021
DOI: 10.1016/j.ajog.2021.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone levels among contraceptive users: evidence from a cross-sectional cohort of 27,125 individuals

Abstract: BACKGROUND: Anti-Mü llerian hormone has become the clinical biomarker-based standard to assess ovarian reserve. As anti-Mü llerian hormone testing becomes more common, more individuals are seeking to interpret the values obtained while using contraceptives. To appropriately counsel women, a better understanding of anti-Mü llerian hormone levels in women using different contraceptives is needed. OBJECTIVE: To study the association between different forms of contraceptives and anti-Mü llerian levels in women of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…Furthermore, of the nine studies that excluded for OCP use, they did so only in the context of recent use (i.e., in the last 2 months). Studies have shown that women on OCP or other hormonal contraceptives display lower AMH levels [ 61 , 62 ] with long-term users having 30% lower AMH levels than non-users [ 63 , 64 ]. This is an important consideration in the context of this review, since hormonal contraception is known to have variable responses in obese populations [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of the nine studies that excluded for OCP use, they did so only in the context of recent use (i.e., in the last 2 months). Studies have shown that women on OCP or other hormonal contraceptives display lower AMH levels [ 61 , 62 ] with long-term users having 30% lower AMH levels than non-users [ 63 , 64 ]. This is an important consideration in the context of this review, since hormonal contraception is known to have variable responses in obese populations [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cross-sectional cohort study conducted with 27,125 participants showed that compared to non-users, AMH levels were lower not only in participants using oral contraceptives but also in those using vaginal rings, hormonal intrauterine devices, implants, and progestin-only contraceptive pills at variable percentages (16).…”
Section: Discussionmentioning
confidence: 96%
“…While many studies have examined the effect of LNG-IUD on uterine bleeding in the literature, very few have investigated its effects on ovarian reserve. Studies on the effects of LNG-IUD on ovarian function generally compare contraceptive methods [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hariton et al [ 22 ] compared AMH among contraceptive users and women not on contraceptives and found that AMH levels were 7% lower in women with hormonal IUD, 15% lower in those taking the progestin-only pill, 22% lower in vaginal ring users, 23% lower in implant users, and 24% lower in those taking COC. They also noted that the AMH level in women using copper IUDs was not significantly different from that in women not using contraceptives.…”
Section: Discussionmentioning
confidence: 99%